Hand hygiene's knowledge, perception and self-reported performance among nurses at tertiary care hospitals in Kelantan, Malaysia - Rahim, Mohamad Hazni Abd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2020)
Introduction: Healthcare-associated infections (HCAIs) represents the most frequent adverse event during care delivery, and there was no institution or country can claim to have solved the problem yet. HCAIs can be reduced as much as 50% if the health care able to improve hand hygiene (HH) practice before and after being with a patient. Monitoring HH practices, knowledge, infrastructure, and perception is an important strategy to improve practices and reduce HCAIs and AMR. Objective: The objective of the current study aims to assess knowledge, perception, self-reported performance scores on HH and to determine factors associated with self-reported performance among nurses at tertiary care hospitals in Kelantan, Malaysia. Methods: A cross-sectional using primary data collection among registered nurses at all tertiary care hospitals in Kelantan was conducted. The data collection was started from 15 December 2019 until 15 February 2020. A stratified random sampling method was applied, with the sample size required was 530. Initially, the first strata were four hospitals, and the next strata were types of the department in each hospital. From the list, simple random sampling was used for all available nurses in each department, proportionate to the number of available nurses. Data were collected using the World Health Organization (WHO) HH knowledge and perception self-administered questionnaires. All domains were adapted consist of socio-demographic and working characteristics, HH knowledge and perception survey. Data were analysed using SPSS version 26.0, and descriptive analysis with multiple linear regression method was applied. Results: A total of 438 participants was included in the study. Majority of the participants were female with a mean age of 38 years old. The general characteristics revealed that almost all were married, and most of them had complete their study at 3-year college/Diploma level. Their average work experience was 14 years. 91.8% of participants had received HH training, 97.5% routinely used hand rub, and only 4.8% were infection control nurses. Their knowledge score was 15.08±1.960; perception score was 68.2±10.144, and self-reported HH performance was 87.58±12.025. The predictors that significantly predict the self-reported HH performance among nurses include perception score (B=0.309; 95%CI:0.200,0.417; p<0.001), paediatrics department (B=-5.901; 95%CI:-9.335,-2.467; p<0.001) and orthopaedics department (B=-5.130; 95%CI: -9.539,-2.287; p<0.023).(Adjusted R² = 0.102; p< 0.001). Conclusions: In summary, overall perception and self-reported HH performance were high, however knowledge score seems to be lower. Lack of HH knowledge during patient care could result in poor HH practices, thus increase HCAIs and AMR. Therefore, strategy for the intervention of HH performance should focusing more on knowledge as well as perception through performing extensive WHO HH multimodal strategy.